Die aard van die genderkonstruksie van vroulike hoofkarakters in resente Afrikaanse jeugliteratuur - Geldenhuys, Isabella Magrieta Christina (Cape Peninsula University of Technology, 2016)
Gender roles for both men and women have changed considerebly during the past two decades. These changes were caused by the New Constitution of South Africa. Women are not limited anymore to certain careers or gender roles. They can live life to their full potential as individuals. The youth are still in a variable state and are influenced by what they read. Youth literature plays a huge role in the construction of gender identity. The way gender is portrayed in youth literature contributes to the view children develop of their own gender. Gender stereotyping, sexism and sexist language in texts could be interpreted as correct and acceptable if teachers are not aware of it and do not point these out. This study was conducted to determine if Afrikaans youth literature changed in accordance to society’s views of gender roles and how youth literature plays a role in the construction of gender. For this study award-winning youth books with a female main character were chosen and were subjected to Critical Discourse Analysis. Critical Discourse Analysis exposes hidden power structures and looks critically at the language used to construct female charaters as well as who the focalizer is and how the focalizer describes the female characters. Research findings showed that there are positive changes in Afrikaans youth literature. Writers are creating stronger female characters for the youth. Research findings also show that certain stereotypes are too deeply rooted and will take more time to change. That is why it is important for the teacher in the classroom to be aware of the hidden power structures and stereotypes in youth literature and to point it out in order to teach in a more gender-sensitive way.
Thesis (MEd (Education))--Cape Peninsula University of Technology, 2016.
Keywords: Gender identity in literature; Women in literature; Sex role in literature; Young adult literature